AUTHENTIC ASSESSMENT TEACHING AND LEARNING TRAJECTORY WITH E-STUDENT ACTIVITY SHEET (E-SAS) TO IMPROVE THE QUALITY OF LEARNING PROCESS - Herianingtyas, Nur Luthfi Rizqa; Rohman, Chaerul; Widiyanto, Rohmat; Amarulloh, Reza Ruhbani (PD PGMI se Indonesia, 2023)
Traditional assessment in education primarily measures the academic performance of learners without reflecting the learning process. Many educators neglect to reflect on their teaching practices for continuous quality improvement. The authentic assessment instrument, Teaching and Learning Trajectory with E-Student Activity Sheet (E-SAS), can identify the profile of teaching and learning trajectories within the syntax of instructional models, enabling educators to determine appropriate corrective measures for each session. The development of this assessment instrument utilized the Research and Development (R&D) method, following the ADDIE model. The study involved 34 students enrolled in a Basic Science Concepts course. Fifteen authentic teaching and learning trajectory test items were developed for three sessions and were validated as